Biocidal potential of Eugenia pyriformis essential oil in the control of Rhipicephalus (Boophilus) microplus in the free-living cycle - Medeiros,Jaqueline P. (2019)
ABSTRACT: Brazil has one of the largest commercial cattle herds in the world, which naturally coexist with an enormous number of parasitic species. Southern cattle tick, Rhipicephalus (Boophilus) microplus, is among these species, interfering with animal productivity and causing losses to the beef and dairy cattle sector. The use of chemical acaricides in the control of this mite has resulted in the emergence of resistant populations. In this sense, alternative control measures using plants as sources of botanical acaricides have shown to be effective. Eugenia pyriformis Cambess is a Brazilian plant with antioxidant and antimicrobial activity; however, there are no reports on its acaricidal activity in the literature. The present study aimed to evaluate the acaricidal and larvicidal potential of E. pyriformis leaf essential oil (EO) on southern cattle tick at different stages of the reproductive cycle. E. pyriformis leaves were collected and dried, and had their EO extracted by hydrodistillation (3h) using a modified Clevenger apparatus. Chemical analysis was performed by gas chromatography coupled with mass spectrometry (GC/MS), and 32 compounds belonging to the sesquiterpene class were identified: hydrocarbons (17.98%) and oxygenated forms (81.96%), with spathulenol (43.65%) and caryophyllene oxide (12.17%) as the most common. The EO was evaluated by the Adult Immersion Test at the concentrations (500.00 to 3.12mg/mL) in which the following parameters were measured: mortality of females (%), hatchability of eggs (%), and product efficiency (%). Larvae were assessed by the Larval Packet Test at concentrations ranging from 25.00 to 0.00004mg/mL. Lethal concentrations (LC) required for killing 50 and 99.9% of adult females and larvae were determined using Probit analysis. LC50 and LC99.9 of EO were 0.06 and 24.60mg/mL and 1,208.80 and 2,538mg/mL for larvae and adult females, respectively. Action of the EO in the free-living cycle of R. (B.) microplus larvae was another parameter assessed. To this end, the larvae were deposited in pots containing Brachiaria decumbens and, after migration to the leaf apex, a solution containing LC99.9 (24.60mg/mL) of the EO was sprayed. After 24h, 72.25% of the larvae had died, indicating stability of the EO when subjected to uncontrolled temperature and humidity conditions. The mechanism of action through which the EO killed the larvae and adult females was investigated by the Bioautographic Method, which showed inhibition of 3.15mg/mL of the EO on the acetylcholinesterase (AChE) enzyme. The results found in the present experiment indicate that E. pyriformis essential oil is an alternative in the control of southern cattle tick in the larval (parasitic) and free-living cycle (non-parasitic) stages under field conditions.